2000
DOI: 10.1007/pl00000651
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling in vertebrate and invertebrate limb patterning

Abstract: Invertebrate and vertebrate limbs have very different anatomies and modes of development. Despite these differences, recent studies demonstrate that a significant overlap exists in the signals used to pattern invertebrate and vertebrate limbs. One of these signaling molecules is Hedgehog, a secreted protein that functions to coordinate growth and proliferation along the anterior-posterior axis of developing limbs. Recent studies indicate that the mechanism of action, regulation and function of Hedgehog signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 99 publications
(81 reference statements)
0
20
0
1
Order By: Relevance
“…However, some mesodermal gene expression was lost. Shh, which depends on ridge FGF signals (reviewed by Capdevila and Johnson, 2000), was absent in T -/-limb buds (Fig. 8D).…”
Section: Potential Late Mesenchymal Effects Of Abnormal Aer Function mentioning
confidence: 95%
See 1 more Smart Citation
“…However, some mesodermal gene expression was lost. Shh, which depends on ridge FGF signals (reviewed by Capdevila and Johnson, 2000), was absent in T -/-limb buds (Fig. 8D).…”
Section: Potential Late Mesenchymal Effects Of Abnormal Aer Function mentioning
confidence: 95%
“…Sonic hedgehog (Shh), expressed in posterior limb bud mesoderm, regulates AP polarity and number of skeletal elements. Activation of Shh also depends on ridge signals and subsequently positive feedback between FGF4 from posterior ridge and SHH maintains both signaling centers (reviewed by Capdevila and Johnson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike reflecting homology between insect wing and vertebrate limbs, this indicates a general function of hh, i.e. control of cellular differentiation and proliferation (Capdevilla and Johnson 2000). Keys et al (1999) demonstrated the recruitment of a hh regulatory circuit in butterfly eyespot generation.…”
Section: The Rostrum or Labrummentioning
confidence: 98%
“…Other proteins such as tout velu, disp (28), and Hip (29) have been shown to affect Shh transport but are not considered in our model. In our model Shh is assumed to diffuse freely and binds to Ptc receptors reversibly.…”
Section: Model Developmentmentioning
confidence: 99%